Clausewitzian friction and autonomous weapon systems. Issue 1 (2nd January 2021) - Gardner, Nikolas
Abstract: In the 1990s, Barry Watts assessed the impact of modern technology on the incidence of general friction in warfare, concluding that the participation of humans in wars made friction nearly impossible to eliminate. The advent of autonomous weapon systems (AWS), however, has the potential to reduce the role of humans significantly. This article considers the impact of AWS on the incidence of friction in future wars. Using Watts' taxonomy of general friction as an analytical tool, it argues that while these weapons have the potential to reduce friction resulting from human limitations, they will likely increase informational uncertainty, and unintended escalation.